Construction history of the aqueduct of Nicaea (Iznik, NW Turkey) and its on-fault deformation viewed from archaeological and geophysical investigations. (October 2018) - Benjelloun, Yacine; de Sigoyer, Julia; Dessales, Hélène; Garambois, Stéphane; Şahin, Mustafa
Abstract: The aqueduct of Nicaea (modern Iznik, in northwestern Turkey) was studied for the first time using combined building stratigraphy, typology of construction techniques and subsurface geophysics. The analysis of the different materials and building techniques used allowed us to identify more than forty individual stratigraphical units on the section investigated, using thirteen specific techniques. The comparison of certain masonries with analogous techniques visible in the defensive walls of the city and our stratigraphical interpretations led us to propose a chronology of the construction divided into nine phases. Some of these rebuildings seem linked to war and earthquake damage. The aqueduct was originally built in the first centuries AD using a framework of terracottas and limestone rubble. Later on, two functional terracotta structures were added and the specus was extensively rebuilt. In a second period, the early facing was replaced by well-cut travertines. Significant rebuilding occurred around the 11th century when the city was attacked by the Turks. The last modifications date from the Lascarid period and are probably linked to the construction of a second defensive wall in the 13th century, which cuts the western end of the aqueduct. Geophysical acquisitions on the eastern section of the aqueduct evidenced a vertical offset of the building. The location of these offsets correlate well with the trace of a normal fault which historical activity was not suspected before. These kind of multidisciplinary approaches are powerful tools to study active tectonics and their impact on past societies. Highlights: The analysis of the building stratigraphy of Nicaea aqueduct evidenced nine main stages of construction. Vertical displacement of the aqueduct correlates with the trace of a normal fault with no historical activity documented. On-fault and off-fault damages on the aqueduct linked to historical earthquakes. Interest of multidisciplinary approach for seismic risk issues.